A Risk Assessment in Natural Gas Supply - Ismail, Mohd Azril; Mohd Sharif, Kamal Imran; Mohamed Udin, Zulkifli; Hassan, Mohamad Ghozali; Mohd Nawi, Mohd Nasrun; Abdul Hamid, Zahril Anwar Malek; Ibrahim, Jafni Azhan; Othman, Abdul Aziz (ExcelingTech Publishers, 2018)
The purpose of this study is to identify the risk of natural gas supply.There are two modes of delivering the natural gas which are the pipeline system and ships.In view of this, there are risks faced by producer in dealing with the supply of natural gas. The risk can be categorized as market risk, supply risk, and transportation risk.Market risk refers to the risk of macroeconomic, supply risk refers to risk of physical distribution in gas supplies and transportation risk refers to a set of accidental leakage scenarios that happen when the delivering occur.